2016
DOI: 10.15252/emmm.201505719
|View full text |Cite
|
Sign up to set email alerts
|

TECRL, a new life‐threatening inherited arrhythmia gene associated with overlapping clinical features of both LQTS and CPVT

Abstract: Genetic causes of many familial arrhythmia syndromes remain elusive. In this study, whole‐exome sequencing (WES) was carried out on patients from three different families that presented with life‐threatening arrhythmias and high risk of sudden cardiac death (SCD). Two French Canadian probands carried identical homozygous rare variant in TECRL gene (p.Arg196Gln), which encodes the trans‐2,3‐enoyl‐CoA reductase‐like protein. Both patients had cardiac arrest, stress‐induced atrial and ventricular tachycardia, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 50 publications
4
129
0
Order By: Relevance
“…Initially identified by linkage analysis in a consanguineous Sudanese family with multiple SCDs among children while playing, subsequent whole exome sequencing (WES) identified mutations in a handful of families and probands in TECRL . 101,102 Each patient demonstrated VT and VF, particularly with exertion, and had SCD. Interestingly, while the subjects had normal QT intervals at baseline, adrenergic stimulation caused QT interval prolongation.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially identified by linkage analysis in a consanguineous Sudanese family with multiple SCDs among children while playing, subsequent whole exome sequencing (WES) identified mutations in a handful of families and probands in TECRL . 101,102 Each patient demonstrated VT and VF, particularly with exertion, and had SCD. Interestingly, while the subjects had normal QT intervals at baseline, adrenergic stimulation caused QT interval prolongation.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 99%
“…AP recordings revealed prolonged APD also suggesting a clinical overlap between TECRL mutation-positive individuals with features of both CPVT and LQTS. 102 At present, the mechanisms by which loss of TECRL function alters SR Ca 2+ -handling or ionic currents resulting in prolonged APD remain unknown.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 99%
“…Since there are still IAD cases without known disease‐causing variants, several studies have focused on the discovery of novel Mendelian disease‐causing loci associated with arrhythmogenic channelopathies. One recent study identified two different variants in the trans‐2,3‐enoyl‐CoA reductase‐like ( TECRL ) gene in three patients with clinical arrhythmias using whole‐exome sequencing 12 . Notably, these patients showed features of both LQTS and CPVT‐like adrenergic VT with a high prevalence of cardiac arrest, atrial tachycardia sometimes triggering ventricular arrhythmias, and normal or mildly prolonged QTc at rest with a QTc increase during adrenergic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Devalla et al () also identified two other unrelated patients, both of whom had experienced stress‐ or exercise‐induced arrhythmias with aborted sudden cardiac arrest, who were also found to be carriers of a novel homozygous mutation in the TECRL gene. In all three case studies, the clinical phenotypes showed overlapping characteristics of two primary arrhythmia syndromes: long QT syndrome (LQTS) and catecholaminergic polymorphic ventricular tachycardia (CPVT).…”
mentioning
confidence: 99%
“…In the case of the Sudanese family reported in this issue of EMBO Molecular Medicine (Devalla et al , ), solving the genetics was made considerably easier by the fact that the condition showed autosomal recessive inheritance and the parents were first cousins. Using whole‐exome sequencing, Devalla and colleagues identified a homozygous loss‐of‐function mutation in a novel gene, called trans ‐2,3‐enoyl‐CoA reductase‐like ( TECRL ), that was present in all affected family members.…”
mentioning
confidence: 99%